The Prevalance of comorbidity in India - Anwar, Khalid (Journal of Commerce and Trade, 2022)
Comorbidity is defined as the presence of one or more chronic non-communicable diseases. Recentlymany articles have illustrated that covid positive person with noncommunicable disease has poor health outcome. Covid positive patients with comorbidity such as diabetes, heart diseases and hypertension are more vulnerable to develop a severe health condition. For this study we have taken data from national family and health survey 2015-16 (NFHS-4 survey). This data is national representative and cross section data. The prevalence of comorbidity is highest in females, rural areas, older age people, and highly educated persons. This highlights the need of healthcare facilities at the time of covid pandemic. This research utilized nationally representative (large scale data) and multi-round data to find the prevalence(occurrence) of diabetes and heart disease comorbidity and explore the comorbidity determinants from the National Family Health Survey (NFHS-4). From this study, female, secondary education, and old age have a positive association with diabetes and heart disease comorbidity in India. Diabetes and heart disease comorbidity exhibit a major difficulty to healthcare directors and can increase costs. This study confirms the evidence based on the size of diabetes and its comorbidity circumstances within its boundaries. The prevalence of comorbidity is highest in females, rural areas, older age groups, and secondary education. Classification-JEL: D15, I14, I15